Characterization of Bacillus velezensis LH023 Isolated From Grass Carp Intestines and Its Beneficial Effects on Growth, Immunity, and Gut Microbiota in Aquaculture - Lihan Liu; Jiaming Huang; Yiling Huang; Zhendong Qin; Fubin Zhang (Aquaculture Nutrition)
In this study, Bacillus velezensis was isolated from the intestines of grass carp and identified as LH023 via 16S rRNA sequencing and morphological analysis. To evaluate its potential as a feed additive in aquaculture, LH023 was supplemented at two concentrations (107, 7 × 107 and 108, 7 × 108 CFU/g) in a 6-week feeding trial, alongside a control group. Enzyme activity assays demonstrated that LH023 supplementation enhanced growth performance and increased intestinal enzyme levels, including α-amylase, lipase, protease (Pro), and trypsin. Real-time quantitative PCR (qRT-PCR) analysis revealed significant downregulation of pro-inflammatory genes (IFN-γ2, c-Rel, NF-κB, p52, IKKβ, and IKKγ) in intestinal tissue, while anti-inflammatory cytokine genes (S6K1, IL-4, and IL-10) were upregulated. Additionally, antioxidant-related genes (CAT, SOD, GSH, and Keap1a) and intestinal barrier markers (ZO-2, ZO-3, and claudin-12) were significantly upregulated in the LH023 treatment groups. 16S rRNA sequencing revealed that the 107 and 108 groups exhibited a higher abundance of beneficial microbiota, including Clostridia, Gammaproteobacteria, Bacteroidia, Deltaproteobacteria, and Bacilli. KEGG pathway analysis identified enrichment in metabolic pathways related to carbohydrate metabolism, cofactor and vitamin metabolism, amino acid metabolism, and lipid metabolism. α-Diversity analysis showed no significant differences in microbial diversity (p >0.05), while β-diversity analysis indicated that the microbial communities in the 107 and 108 groups were distinct from the control, with low inter-group similarity. Histological examination (hematoxylin–eosin (HE) and periodic acid–Schiff (PAS) staining) of intestinal, liver, and kidney tissues demonstrated that LH023 supplementation effectively mitigated the tissue damage caused by Aeromonas hydrophila infection and significantly improved grass carp survival. These results suggest that B. velezensis LH023 holds promise as a beneficial probiotic in aquaculture.